Relasi Fikih dan Hadis dalam Praktik Pemahaman Kontekstual Ibn 'Abd al-Barr al-Andalusy (W. 463 H) - Fiki Khoirul Mala; Ahmad Fudhaili (Diroyah : Jurnal Studi Ilmu Hadis, 2022)
The meaning related to contextual understanding as one of the analytical tools in understanding religious texts needs to be understood properly. Combining hadith scholarship and social jurisprudence is one of the efforts made by many hadith scholars in interpreting traditions that are considered irrelevant to the times, one of which is Ibn 'Abd al-Barr al-Andalusy (463 H). This study aims to present the perspective of Ibn 'Abd al-Barr al-Andalusy in carrying out countyer efforts on the thought of the al-Ẓāhiri textual group in Andalusia in the 5th century Hijriyah. This research is a type of qualitative research using hadith and social fiqh approaches that involve the study of text and context. The main data presented are in the book Al-Tamhīd limā fī al-Muwaṭṭa min al-Ma'āni wa al-Asānid by Ibn 'Abd al-Barr al-Andalusy and the book Al-Muḥalla wa al- Ibn Hazm's Athār as a comparison of the āhiriyah group. The results of this study indicate that Ibn 'Abd al-Barr in doing syarah hadith still pays attention to the scientific rules of hadith as well as criticism of sanad and matan, but by using fiqh reality can be found new meanings according to the needs of society at that time and also today. In other words, the presence of Ibn 'Abd al-Barr was able to solve the problem of shari'a in the classical age which is considered irrelevant in this modern age.